PENGARUH MEDIA EDUKASI VIDEO ANIMASI TERHADAP PENGETAHUAN POLA TIDUR SEHAT UNTUK PENCEGAHAN HIPERTENSI PADA REMAJA (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Indonesia is experiencing a change in disease trends from infectious diseases to non-communicable diseases. It is influenced by behavioral and environmental factors. Hypertension is one of the most dangerous health problems, the hypertension rate in Indonesia is quite high at 34.11%. West Java Province has a prevalence of hypertension at the age of 18-24 years at 16.65%. Sleep patterns have a greater risk of hypertension than age and gender. Purpose: knowing whether there is an influence of animation video educational media on knowledge of healthy sleep patterns for the prevention of hypertension in grade 2 adolescents at Darul Falah High School, West Bandung Regency. Method: This study used a pre-experimental design with a one group pretest–posttest without control design with a sample of 81 students. Data analysis used the wilcoxon test to prove the research hypothesis. Results: The average knowledge score of respondents before being given the intervention was 55.11 and the average knowledge score of the respondents after the intervention was 78.55. The percentage increase in knowledge was 23.44%. There is an influence of video educational media on adolescent knowledge with Nilap P = 0.000. Video animation can help stimulate the senses of sight and hearing at the time of receiving information and improve a person's memory. Conclusion: there is an influence of animation video educational media on knowledge about healthy sleep patterns for the prevention of hypertension in grade 2 adolescents at Darul Falah High School, West Bandung Regency.